Mechanisms by which cleaved kininogen inhibits endothelial cell differentiation and signalling - Colman, Robert W.; Wu, Yi; Liu, Yuchuan (Thrombosis and Haemostasis, 2010)
We have shown that cleaved high-molecular-weight kininogen inhibits endoththelial cell tube and vacuole formation in a concentration-dependent manner and this correlates with its recognised anti-angiogenic activity. The antibody against the urokinase plasminogen activator receptor (uPAR) mimicked the inhibitory effect of cleaved kininogen (HKa) on apoptosis (HKa: 30% and uPAR antibody: 26%) and tube formation. In tumour angiogenesis, cancer cells release angiogenic stimulators, such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), thus stimulating the transformation of endogenous pro-uPA to uPA. The proteolytic enzyme urokinase plasminogen activator (uPA) then binds to its receptor in a complex with its inhibitor PAI-1, which results in the internalisation of this complex, and activates extracellular signal-regulated kinase (ERK). Recycling of the uPAR regulates the migration of endothelial cells (ECs). ERK activation stimulates migration and proliferation and suppresses apoptosis of ECs. HKa disrupted the uPA-uPAR complex, inhibited ERK activation, and blocked the internalization of uPAR, eventually resulting in cell death and cell motility arrest. Both are critical steps in angiogenesis.
Keywords: Urokinase / receptor; tissue factor / factor VII; endothelial cells; contact phase; cytokines